Case reportAmyloid goiter as the evidence in secondary amyloidosis in a patient with rheumatoid arthritis - Chemperek, Ewa; Majdan, Maria; Kurowska, Maria; Piotrowski, Mariusz (Reumatologia/Rheumatology, 2006)
Amyloidosis represents not a single disease but a group of diverse pathological processes which can affect any organ or tissue in the body. AA amyloidosis occurs secondary to chronic infections or as a complication from tissue injury, recurrent long-standing inflammatory and autoimmune diseases, most frequently rheumatoid arthritis. Amyloid goiter is an extremely rare condition associated with a clinically apparent enlargement of the thyroid due to massive amyloid infiltration. Amyloid deposition in secondary amyloidosis frequently involves the thyroid gland, but rarely results in a clinically palpable goiter. Expanding mass can cause dyspnoea, dysphagia and hoarseness. We present a 57-year-old woman with amyloid goiter due to rheumatoid arthritis, who developed thyrotoxicosis resembling Hashimoto’s thyroiditis. She noticed neck swelling with severe neck tenderness, palpitations, hyperhydrosis and weight loss. Her serum free T4 and T3 were high, TSH was suppressed to subnormal, anti-thyroid autoantibodies were positive. Surgical therapy is aimed at avoidance of the existing and threatening consequences of expanding mass. The diagnosis of amyloid goiter should be suspected in patients with a diffusely enlarging thyroid gland and an appropriate clinical history.